Educational Intervention Improves Clinician Infection Prevention Knowledge and Behavior in a Pediatric Emergency Department. (October 2020) - Linam, Matthew; Rangwalla, Nikita; Shroff, Purvi; Armstead, Christopher; Beiter, James
Abstract : Background: Children with contagious illness are frequently cared for in the pediatric emergency department. Incomplete infection prevention knowledge and incorrect practices create opportunities for transmission of pathogens. We implemented an educational intervention to improve clinician infection prevention knowledge and behavior. Methods: Clinicians providing care in an academic tertiary-care affiliated, pediatric ED were invited to participate in a 3-month educational intervention focusing on basic infection prevention principles such as hand hygiene and symptom-based isolation. Qstream, an educational platform that employs spaced-learning and game theory, was used to develop and electronically distribute 7 scenario-based questions. Questions were distributed 1 question per day 3 times per week. Questions were repeated until they were answered correctly twice. Round 1 of questions began in March 2019. After a ~4-week hiatus, the process was repeated in May 2019 (round 2). The Kirkpatrick model was used to measure the effectiveness of the educational intervention. Outcomes included clinician assessment of acceptability of the intervention, change in correct responses to knowledge-based questions over time, hand hygiene performance of clinicians and the number of infectious exposures in the emergency department. Results: Overall, 61 (73%) clinicians participated, of whom >90% liked the format, found it easy to use, and thought it required an appropriate amount of time. During round 1, average proficiency increased from 36% to 64%. During round 2, average proficiency increased from 62% to 78%. Starting in May 2019, physician hand hygiene gradually increased from a baseline of 78% to 100%. In the 10 months before and after March 2019, there were 2 exposure events involving 10 healthcare personnel versus 3 exposure events involving 4 healthcare personnel. Conclusions: Novel education strategies that utilize adult learning principles are user-friendly effective strategies that improve infection prevention knowledge and practice. Funding: None Disclosures: None